Fragments of the bacterial toxin microcin B17 as gyrase poisons. - Frédéric Collin; Robert E Thompson; Katrina A Jolliffe; Richard J Payne; Anthony Maxwell (PLoS ONE)
Fluoroquinolones are very important drugs in the clinical antibacterial arsenal; their success is principally due to their mode of action: the stabilisation of a gyrase-DNA intermediate (the cleavage complex), which triggers a chain of events leading to cell death. Microcin B17 (MccB17) is a modified peptide bacterial toxin that acts by a similar mode of action, but is unfortunately unsuitable as a therapeutic drug. However, its structure and mechanism could inspire the design of new antibacterial compounds that are needed to circumvent the rise in bacterial resistance to current antibiotics. Here we describe the investigation of the structural features responsible for MccB17 activity and the identification of fragments of the toxin that retain the ability to stabilise the cleavage complex.